NSAID Carprofen Structure-based Derivatives as potential antibacterial agents - Nitin Kumar; Pallavi Manish Lavhale (Asian Journal of Pharmaceutical Research and Development, 2024)
Drug repurposing (DR) is the use of existing drug in new alternative therapeutic role. Antibacterial perspective of non-antibiotic drugs includes NSAIDS are very useful to combat in a variety of infections in clinical practice. Carprofen (2-(6-chloro-9H-carbazol-2-yl)propanoic acid), is a NSAIDS category drug based on potential pharmacophore tricyclic carbazole nucleus, now commonly used in veterinary medicine. This carprofen drug is used in osteoarthritis and postoperative pain in dogs. Around the worldwide, researchers’ significantly revealed drug repurposing role of carprofen structure-based derivatives as antibacterial agents. These carprofen structure-based compounds displayed excellent antibacterial activities against gram positive as well as gram-negative bacterial strains in review literature. Some carprofen derivatives also displayed potential antibiofilm activity. Multi-target direct ligand (MTDLs) strategy also used to design novel carprofen integrated molecules tethered with potential bioactive pharmacophore like coumarin, 1,3,4-oxadiazole, hydrazide etc. also showed significant in vitro antibacterial activities. Articles related to carprofen as antibacterial agents collected on PubMed, Science direct and Google scholar mainly. However, less research works done on this topic. This review highlighted antibacterial potential of new carprofen derivatives based on carbazole structure tested against bacterial strains with their target mechanism based on literature.